Release of mobile forms of hazardous elements from glassworks fly ash into soils - Udatný, Martin; Mihaljevič, Martin; Šebek, Ondřej (Environmental geochemistry and health, 2014)
The release of hazardous elements from the wastes of high-temperature processes represents a risk to the environment. We focused on the alteration of fly ash (FA) from glassworks collected from an electrostatic filter. FA contains elevated concentrations of Zn and Ba, among other elements. Overtime, small amounts of FA have been emitted from the factory and settled into the surrounding environment (soil). In order to assess the possible risks to the environment, samples of FA were placed in small nylon bags and deposited in 11 different soil horizons (containing diverse vegetation cover such as spruce and beech and also unforested areas). Samples of the FA in bags were exposed in the soils for 1 year. Then, the bags were collected, and the exposed soils in the direct vicinity of the FA bags were sampled. The total concentrations of Zn and Ba in the FA, as well as in the soil samples (original and exposed), were determined by ICP MS. The "mobile fraction" was determined as the exchangeable (acid extractable) fraction of the modified BCR sequential extraction procedure (SEP). The SEP results indicate that Zn and Ba may pose a potential environmental risk. Their concentrations in the first, most mobile, and bioavailable fraction increased in all the exposed soils. The most significant increases were observed in the upper soil horizons (litter and A horizon). The risk to the environment was evaluated on the basis of the Risk Assessment Code.
Keywords: Zinc; monitorování životního prostředí; Soil Pollutants; zinek; Barium; Soil; baryum; chemická frakcionace; látky znečišťující vzduch; Air Pollutants; Chemical Fractionation; půda; Environmental Monitoring; látky znečišťující půdu